Leveraging Mobile Technology to Increase Breastfeeding Rates in Los Angeles County (LAC) [18B]. (May 2016) - Lopez, Leslie; Resser, Lonnie; Rodriguez, Nancy; Ramos, Diana
Abstract : INTRODUCTION: Breastfeeding has health benefits for mothers and infants including less risk of developing obesity and type II diabetes. In the U.S., 97% of reproductive age women of all socio-economic levels (SEL) and ethnicities own cell phones and 73% send and receive text messages. Text messaging has been demonstrated to be a powerful tool in effecting behavior change. Providing health education, motivation, and reminders through mobile technology is an innovative way to improve breastfeeding rates by leveraging a tool that women are already using. METHODS: The Choose Health LA Moms pilot program enrolled 46 postpartum mothers of diverse ethnicities and SEL 2 weeks postpartum. Participants received a weekly text message and e-lessons for 6 months that promoted breastfeeding. Monthly questionnaires assessed participant progress. Quantitative and qualitative data were analyzed. RESULTS: 93.5% (43/46) reported using text messaging daily and sending an average of 15 text messages a day. 67% (31/46) stated that they breastfed more as a result of reading the curriculum. 57% (26/46) stated that receiving the text messages encouraged them to breastfeed more. At baseline, 48% (22/46) were exclusively breastfeeding. When participants completed the program 57% (26/46) were exclusively breastfeeding. 22% (6/27) of those who started out combination feeding switched to exclusive breastfeeding. CONCLUSION: Mobile technology has proven to be effective in providing breastfeeding support and subsequently increasing breastfeeding rates. We demonstrated how leveraging the preferred communication for reproductive women can provide the platform to increase breastfeeding despite their socio economic status.